High Mobility Group Box-1 and Pro-inflammatory Cytokines Are Increased in Dogs After Trauma but Do Not Predict Survival - Goggs, Robert; Letendre, Jo-Annie (Frontiers in Veterinary Science, 2018)
Trauma is common in dogs and causes significant morbidity and mortality, but it remains challenging to predict the prognosis of dogs with traumatic injuries. This study aimed to quantify plasma high-mobility group box-1 (HMGB-1) and cytokine concentrations in dogs with moderate-to-severe trauma, and to evaluate the association between these biomarkers and the injury severity and survival to discharge. Using a prospective, observational case-control study design, 49 dogs with an animal trauma triage (ATT) score ≥3 were consecutively enrolled from 07/2015 to 10/2017 and followed to hospital discharge. Dogs <3 kg and those with pre-existing coagulopathies were excluded. 33 healthy control dogs were also enrolled. Illness and injury severity scores including the acute patient physiologic and laboratory evaluation (APPLE) were calculated using at-presentation data. Plasma HMGB-1 concentrations were measured by ELISA; concentrations of 13 cytokines were measured using multiplex bead-based assays and separately concentrations of 4 cytokines were measured using a multiplex canine-specific ELISA. All biomarkers were measured in duplicate. Mann-Whitney U tests were used to compare biomarker concentrations between groups and between survivors and non-survivors. Associations between biomarkers were evaluated using Spearman’s correlation coefficients. Independent predictors of survival were identified using multivariable logistic regression. Alpha was set at 0.05. Plasma concentrations of HMGB-1, interleukin-6, C-X-C motif chemokine-8, keratinocyte chemoattractant-like and C-C chemokine ligand-2 were significantly greater in injured dogs versus controls (all P≤0.011). In univariate analyses, HMGB-1 was significantly greater in non-survivors 46.67 ng/mL (8.94-84.73) compared to survivors 6.03 ng/mL (3.30-15.75), (P=0.003). Neither HMGB-1 or the cytokines were associated with survival independent of illness severity as measured by the APPLE score, however.